-2/3(e-3)-3=4(1-e)

Simple and best practice solution for -2/3(e-3)-3=4(1-e) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/3(e-3)-3=4(1-e) equation:


(-2/3)*(e-3)-3 = 4*(1-e)

-2/3*(e-3)-3 = 4*(1-e)

-2/3*(e-3)-(4*(1-e))-3 = 0

-4*(1-e)-2/3*(e-3)-3 = 0

-2/3*(e-3)-4*(1-e)-3 = 0

L <> R

See similar equations:

| m=j/d | | -9x-141+x=67 | | -3.4*0.2+8*0.2x=0 | | -50+9x-6x=19 | | 7b^2=-55b+8 | | -2.3*0.2+6*0.2x=0 | | 2m^6-9m^3+7m^7-3m^5= | | -164+4x+6x=66 | | 245x^2-75=70x | | 2i+2+(3i-4)=16 | | -3x/x-x^2 | | 8-4(2+10)/12 | | y=1/5x-1-10 | | 5v^2=-31v-28 | | -26-2x+5x=22 | | 5(4q-1)=2q+7 | | a/2=2.5-3a | | 42/6+5 | | 3s+4t=18 | | 0=4x^2-340x+3000 | | 2x^2+35=19x | | -76-5x-11x=116 | | 15k^2-4k=4 | | 2(6x+1)= | | -119-4x+11x=42 | | 0=4x^2+340x+3000 | | 5(u-5)=2(u-14) | | -58.68-80.24=4z-83.81 | | 56x^2+336=-440x | | -x^2+8x=-7 | | 40d+0.25=25d+0.45 | | s=21/0.75 |

Equations solver categories